Food inauthenticity: Authority activities, guidance for food operators, and mitigation tools. Issue 6 (18th October 2022) - Popping, Bert; Buck, Neil; Bánáti, Diána; Brereton, Paul; Gendel, Steven; Hristozova, Nevena; Chaves, Sandra Mourinha; Saner, Samim; Spink, John; Willis, Charon; Wunderlin, Daniel
Abstract : Abstract: Historically, food fraud was a major public health concern which helped drive the development of early food regulations in many markets including the US and EU market. In the past 10 years, the integrity of food chains with respect to food fraud has again been questioned due to high profile food fraud cases. We provide an overview of the resulting numerous authoritative activities underway within different regions to counter food fraud, and we describe the guidance available to the industry to understand how to assess the vulnerability of their businesses and implement appropriate mitigation. We describe how such controls should be an extension of those already in place to manage wider aspects of food authenticity, and we provide an overview of relevant analytical tools available to food operators and authorities to protect supply chains. Practical Application : Practical Application of the provided information by the food industry in selecting resources (guidance document, analytical methods etc.)